Anisotropic solar wind sputtering of the lunar surface induced by crustal magnetic anomalies. Issue 14 (22nd July 2014) - Poppe, A. R.; Sarantos, M.; Halekas, J. S.; Delory, G. T.; Saito, Y.; Nishino, M.
Abstract The lunar exosphere is generated by several processes each of which generates neutral distributions with different spatial and temporal variability. Solar wind sputtering of the lunar surface is a major process for many regolith‐derived species and typically generates neutral distributions with a cosine dependence on solar zenith angle. Complicating this picture are remanent crustal magnetic anomalies on the lunar surface, which decelerate and partially reflect the solar wind before it strikes the surface. We use Kaguya maps of solar wind reflection efficiencies, Lunar Prospector maps of crustal field strengths, and published neutral sputtering yields to calculate anisotropic solar wind sputtering maps. We feed these maps to a Monte Carlo neutral exospheric model to explore three‐dimensional exospheric anisotropies and find that significant anisotropies should be present in the neutral exosphere depending on selenographic location and solar wind conditions. Better understanding of solar wind/crustal anomaly interactions could potentially improve our results.